A short history of Italy, from classical times to the present day (University Press, 1963)
This is an excellent and readable introduction to Italian history. A mong others there are sections on Rome, the Holy Roman Empire, the Papacy and the Renaissance; on the centuries of foreign domination, first by Spain, then by Napoleon, until th country became finally united,....